Clinic manifestations in granulomatosis with polyangiitis. (June 2016) - Greco, A; Marinelli, C; Fusconi, M; Macri, GF; Gallo, A; De Virgilio, A; Zambetti, G; de Vincentiis, M
Granulomatosis with polyangiitis (GPA), formerly Wegener's granulomatosis (WG), is an uncommon immunologically mediated systemic small-vessel vasculitis that is pathologically characterised by an inflammatory reaction pattern (necrosis, granulomatous inflammation and vasculitis) that occurs in the upper and lower respiratory tracts and kidneys. Although the aetiology of GPA remains largely unknown, it is believed to be autoimmune in origin and triggered by environmental events on a background of genetic susceptibility. In Europe, the prevalence of GPA is five cases per 100, 000 population, with greater incidence in Northern Europe. GPA can occur in all racial groups but predominantly affects Caucasians. Both sexes are affected equally. GPA affects a wide age range (age range, 8–99 years). Granulomatosis with polyangiitis is characterised by necrotising granulomatous lesions of the respiratory tract, vasculitis and glomerulonephritis. Classically, the acronym ELK is used to describe the clinical involvement of the ear, nose and throat (ENT); lungs; and kidneys. Because the upper respiratory tract is involved in 70–100% of cases of GPA, classic otorhinolaryngologic symptoms may be the first clinical manifestation of disease. The nasal cavity and the paranasal sinuses are the most common sites of involvement in the head and neck area (85–100%), whereas otological disease is found in approximately 35% (range, 19–61%) of cases. Diagnosis of GPA is achieved through clinical assessment, serological tests for anti-neutrophil cytoplasmic antibodies (ANCA) and histological analysis. The 10-year survival rate is estimated to be 40% when the kidneys are involved and 60–70% when there is no kidney involvement. The standard therapy for GPA is a combination of glucocorticoids and cyclophosphamide. In young patients, cyclophosphamide should be switched to azathioprine in the maintenance phase. A multidisciplinary approach, involving otorhinolaryngologists, oral and maxillofacial surgeons, oral physicians, rheumatologists, renal and respiratory physicians, and ophthalmologists, is necessary for the diagnosis and therapeutic treatment of GPA. ENT physicians have a determining role in recognising the early onset of the disease and starting an appropriate therapy.